The Relationship between Metabolic Effects and the Hormone Cortisol on Anxiety Disorder Patients Treating at Madani Hospital Medan - Nuralita, Nanda Sari (Universitas Aisyah Pringsewu, 2024)
Introduction: Anxiety disorder is a condition that is often found in society in general. Long-term anxiety disorders can cause an increase in the hormone adrenaline resulting in an increase in free fatty acids and blood glucose levels, and also cause the release of the hormone cortisol, which is a glucocorticoid hormone synthesized from cholesterol in the adrenal cortex, which can have a negative impact on cardiovascular, metabolic and respiratory effects. Cortisol is commonly known as the